Graphene Nanoribbons: An Effective Approach to Achieve a Spin Gapless Semiconductor–Half‐Metal–Metal Transition in Zigzag Graphene Nanoribbons: Attaching A Floating Induced Dipole Field via π–π Interactions (Adv. Funct. Mater. 12/2013). (13th March 2013) - Guan, Jia; Chen, Wei; Li, Yafei; Yu, Guangtao; Shi, Zhiming; Huang, Xuri; Sun, Chiachung; Chen, Zhongfang
<x xml:space="preserve">Abstract</x> On page 1507, Guangtao Yu, Xuri Huang, Zhongfang Chen, and co‐workers report that by attaching a floating induced dipole field via π–π interactions, spin gapless semiconducting (SGS)–half‐metallic–metallic transitions can be achieved in zigzag graphene nanoribbons. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>